2017
DOI: 10.5468/ogs.2017.60.3.289
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic and obstetric outcomes of conservative surgery for borderline ovarian tumors in women of reproductive age

Abstract: ObjectiveTo compare the oncologic and obstetric outcomes in reproductive-age females with borderline ovarian tumors (BOTs) treated with cyst enucleation (CE) or unilateral salpingo-oophorectomy (USO).MethodsThe medical records of patients with BOTs treated between 1998 and 2014 were retrospectively reviewed. The recurrence rates in the USO and CE groups were compared, and the postoperative obstetric outcomes were assessed via telephone survey.ResultsEighty-nine patients with BOTs underwent USO, and 19 underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Recently, Lee et al compared two subtypes of fertility sparing surgery for borderline ovarian tumors and found they had a high rate of pregnancy after surgery where 79.2 and 87.5% respectively of the patients were able to conceive and most carried to term. 13 Similar results were published by Song in 2011 and Park in 2009 with fertility rates upwards of 70% but in 2011 Kanat Pektas had a rate of only 52%. [14][15][16] A meta analysis by Vasconcelos in 2015 revealed an overall rate of approximately 50-60% and was consistent with a previous meta analysis done by Darais in 2011.…”
Section: Discussionsupporting
confidence: 77%
“…Recently, Lee et al compared two subtypes of fertility sparing surgery for borderline ovarian tumors and found they had a high rate of pregnancy after surgery where 79.2 and 87.5% respectively of the patients were able to conceive and most carried to term. 13 Similar results were published by Song in 2011 and Park in 2009 with fertility rates upwards of 70% but in 2011 Kanat Pektas had a rate of only 52%. [14][15][16] A meta analysis by Vasconcelos in 2015 revealed an overall rate of approximately 50-60% and was consistent with a previous meta analysis done by Darais in 2011.…”
Section: Discussionsupporting
confidence: 77%
“…Zhao [20] reported a total pregnant rate of 33.8%. Lee also reported that 26 of the 32 patients (81.3%) had successful pregnancies [16]. A systematic review of 230 articles on conservative management of BOTs reported the pregnancy rates ranged from 32-88%, and the pooled estimate for spontaneous pregnancies was 54% (95% CI: 38-70%, I 2 = 91%) [21] .…”
Section: Discussionmentioning
confidence: 98%
“…A large cohort study on BOT of the Arbeitsgemeinschaft Gynaekologische Onkologie (AGO ROBOT study) con rmed ISS as an independent negative prognostic factor for disease recurrence, apart from other factors such as higher IFGO stage, residual tumour, and fertility preservation [15] . Generally, fertility preservation for BOT patients carries a good prognosis [16][17][18][19] . But few studies have discussed the safety and necessity of CSS for BOTs in FSS.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen studies compared the risk of BOT recurrence between patients underwent unilateral salpingooophorectomy and unilateral/bilateral cystectomy (Table 2) [12,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], and the results of the pooled analysis revealed that the rate of tumor relapse was significantly higher in patients receiving unilateral/bilateral cystectomy (OR=2.02, 95% CI: 1.59-2.57, P < 0.001, Fig. 1).…”
Section: Comparison Of Postoperative Recurrence Risk Between Patients With Unilateral Salpingo-oophorectomy and Unilateral/bilateral Cystmentioning
confidence: 99%